Hubungan Pengetahuan Tentang Anemia Gizi Besi Dengan Tingkat Konsumsi Protein Dan Zat Besi Pada Remaja Putri di Ponpes Asy-Syarifah Desa Brumbung Kabupaten Demak - Rizky Afrilia Putri; Agustin Syamsianah; - Mufnaetty (Jurnal Gizi, 2013)
Anemia in adolescent girls is still a of nutrition problem in Indonesia. HouseholdHealth Surveys Data (SKRT) revealed that the prevalence of anemia in adolescent girls 51.7%. Various factors can affect the occurrence of anemia in adolescentsamong others, future growth, feeding habits, menstrual patterns, knowledge of anemia and of nutrition status. Preliminary results of observations committed against 10 santri in February 2013 showed that women students consumption of 2-3x per day more often 75% of vegetable side dishes and vegetables 25%, whereas only 25% animal-free side dish within 1 week. Thepurpose of this study was to determine the relationship of knowledge about iron nutrition anemia consumption levels of protein and iron in adolescent girls Pondok Pesantren in the village of Asy-Syarifah Brumbung Demak regency. Types of research used analytic research, that is describes the relationship between a dependent variable (the level of consumption of protein and iron) with the independent variables (knowledge anemia). The method used was a questionnaires a survey with the tool and food recall conducted not in a row. The approach used (cross-sectional), where the cause and effect variable researched and measured in the same time. Population taken in this study is which women students are still adolescents (aged 13-18th) on 17-22 June 2013 by 30 santriwati in Ponpes Asy-Syarifah Brumbung the village of Demak regency. Samples were taken from all members of the population. The results showed that the majority presentation shows women students with the the knowledge categories were 18 persons (60.0%), most of the good the level of protein consumption category 22 people (73.3%), whereas most iron consumption the level of categories of deficit by 16 people (53.3%). Results of data analysis using Pearson correlationtest and obtained results that the p-value (p = 0.022) there is knowledge of the relationship of anemia with the protein consumption level and p-value (p = 0.740) then there is no knowledge of the relationship of anemia with the iron consumption level. Need a suggestion for santriwati counseling and provide book about iron nutrition anemia to add a knowledge less especially adolescent girls Pondok Pesantren expected the girls to pay attention to the provision of balanced nutritional value of food, which can be done by working together on a a nutritionist at the health center. Need to conducted a routine check anemia in adolescent girls with health services. There needs to be good cooperation between Ponpes with the health services in order to monitor the health of the santri.